Chromosome Aberrations as a Biomarker for Genomic Instability in Cell Cultures Originated From Bovines, Canines and Equines Infected With Papillomavirus - Simões, Rachel Siqueira de Queiroz; Barth, Ortrud Monika (International Journal of Applied Sciences and Biotechnology, 2016)
Chromosomal abnormalities or aberrations were investigated in ten bovines, three canines and three equines presenting cutaneous papillomatosis. The aim of the present study was to evaluate possible chromosomal abnormalities as a biomarker of genomic instability induced by the interaction of the viral genome with the chromatin of the host cell in peripheral blood lymphocytes and skin warts lesion cultures. Genomic DNA was extracted from blood samples and epithelial biopsies. Amplification products from PCR using degenerated primer pair FAP59/FAP64 were sequenced. Peripheral blood lymphocytes and tumor cell cultures were performed. Structural chromosomal aberrations were verified as associations, chromosomal fragments, centric fusions, open chromatids, gaps, rearrangements and rings. Several levels of premature chromosome condensation were observed in both cultures. Numeric abnormalities as aneuploidy were also detected and hipoployd cells were found in a larger number than the hiperployd cells. This cytogenetic study in detecting premature chromosome condensation in the three species investigated describes by the first time the structural and numerical abnormalities in canines and equines presenting papillomatosis lesions. These abnormalities are similar of the three groups of animals, but virus specific. Int J Appl Sci Biotechnol, Vol 4(1): 104-112